2017
DOI: 10.1021/acs.jpcc.7b00239
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Functionalities Evolution in Thermally Treated Graphene Oxide Featured by EELS and DFT Calculations

Abstract: The local atomic configuration of graphene oxide (GO) was investigated by identifying the different oxygen functionalities and following their evolution induced by thermal treatments in various environments (vacuum, nitrogen or argon flow). X-ray photoelectron spectroscopy and scanning transmission electron microscopy analyses were performed, and electron energy-loss (EEL) spectra were acquired in different regions of GO and thermally reduced GO flakes. Experimental results show a series of characteristic peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 26 publications
(71 reference statements)
5
36
0
2
Order By: Relevance
“…Further it has been reported based on molecular dynamic simulations that desorption of C-OH groups during thermal treatment introduce minimal disorder to the basal plane structure, whereas the destruction is much larger with C-O-C reduction [56]. It is also important to note that the TGA analysis was carried out under identical conditions for all samples, thus eliminating the environmental effect for the observed changes in the thermographs [66]. Therefore, the observed change in the thermal behavior of GO4 to that of GO1, GO2, and GO3 can be related to the special distribution of the oxygen functionalities, especially that of C-OH and C-O-C on the above samples.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Further it has been reported based on molecular dynamic simulations that desorption of C-OH groups during thermal treatment introduce minimal disorder to the basal plane structure, whereas the destruction is much larger with C-O-C reduction [56]. It is also important to note that the TGA analysis was carried out under identical conditions for all samples, thus eliminating the environmental effect for the observed changes in the thermographs [66]. Therefore, the observed change in the thermal behavior of GO4 to that of GO1, GO2, and GO3 can be related to the special distribution of the oxygen functionalities, especially that of C-OH and C-O-C on the above samples.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…After oxidation, we observed the obvious development of additional peak at 288.6 eV that can be attributed to COC oxygen epoxy bonds or COH carboxylic groups . Taking into account that several studies show that the epoxides disappear after thermal treatments at temperatures between 150 and 450 °C, while hydroxyl and carboxylic groups survive and are stable up to 1000 °C it can be suggested that additional peak comes from carboxylic groups.…”
Section: Resultsmentioning
confidence: 75%
“…Such shift can be attributed to the highly disordered structure with mixing sp 2 and sp 3 CC bonds as well as to the presence of O chemically bonded to C in the form of hydroxyl groups. It is well known that incorporation of O in carbon structures results in appearing of specific spectral features in the range of 285–290 eV caused by excitation of π* states of CO bonds in form of epoxy bridges, hydroxyl, carboxyl, and carboxylate groups …”
Section: Resultsmentioning
confidence: 99%
“…It shall be mentioned, though, that especially these two signals allow for a lot of different interpretations and are heavily discussed in literature. In other reports, the signal around 288.9 eV was assigned to CQO transitions related to COOH groups, 59,60 interlayer states, 61 as well as contaminant effects on the GO surface. 6 Although our theoretical study cannot rule out the possibility of interlayer effects or contaminants, we can confirm that the signal at 288.9 eV is, in principle, describable as p*(CQO) related transition from both carbonylic as well as carboxylic group XA spectra.…”
Section: Figmentioning
confidence: 82%